Clinico mycological study of tinea capitis - K., Geetha; S., Nithya priyadharshini (International Journal of Research in Dermatology, 2017)
Background: Tinea capitis is a superficial fungal infection of the scalp and scalp hair that is caused by dermatophytes most commonly in children. It is caused by genera Trichophyton and Microsporum.The aims and objectives of the study were to study the epidemiological aspects, various etiological agents, clinical types, clinic etiological correlation and to note the changing trends. Methods: All new patients with tinea capitis were included for the study after KOH positivity. For total 98 patients in all age groups, fungal culture was performed from scalp scrapings. The epidemiological factors and the clinic etiological correlation were also assessed. Results: Tinea capitis was found most commonly in the 5-10 years age group with a male preponderance (69%). Non inflammatory types were more commonly observed in 66.3% of cases, with grey patch being the most common type. Kerion was most common in inflammatory group. T. tonsurans (31.1%) was the most frequently isolated fungus followed by T. violaceum and T. mentagrophytes in 25.7% each. In previous studies T. violaceum was the most common agent isolated in South India, whereas T. tonsurans is the most common agent in this study, showing a changing scenario. The clinic mycological correlation revealed that a single pathogen may give rise to various clinical types. Conclusions: In any location, the pathogenic species may change with time. A single pathogen may give rise to various clinical types.